2018
DOI: 10.1016/j.jor.2018.01.003
|View full text |Cite|
|
Sign up to set email alerts
|

Do demographic and perioperative parameters really affect the final outcomes of pediatric femur shaft fractures managed by elastic nails? A prospective study

Abstract: Intramedullary TENS is an excellent modality to treat femoral shaft fractures in patients of school going age. However, factors like weight of the patient >40 kg, immobilization beyond 6 weeks, minor and major complications in the perioperative period could pose risks for poor to satisfactory outcomes and should be anticipated and explained accordingly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
6
0
2
Order By: Relevance
“…It is important to return the child to the family environment as soon as possible, and to reduce the cost of care for the patient. 8,9 This will reduce the psychological negative effects of the child, as well as it will benefit the family and the child as social and economic 10,11…”
Section: Introductionmentioning
confidence: 99%
“…It is important to return the child to the family environment as soon as possible, and to reduce the cost of care for the patient. 8,9 This will reduce the psychological negative effects of the child, as well as it will benefit the family and the child as social and economic 10,11…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al compared the fixation of subtrochanteric fractures in children with FIN and locking plates and found two methods can result in good functional outcomes, and the ranges of motion and neck-shaft angle of the affect limb were almost the same as those of the unaffected side in both methods [17]. Reddy et al presented a series of cases treated with FINs and showed that fracture located in the proximal region of the femur presented satisfactory outcome at end of 12 months [25]. Nevertheless, the number of cases was small, and restrictions of activities were recommended post-operatively [25].…”
Section: Discussionmentioning
confidence: 99%
“…Reddy et al presented a series of cases treated with FINs and showed that fracture located in the proximal region of the femur presented satisfactory outcome at end of 12 months [25]. Nevertheless, the number of cases was small, and restrictions of activities were recommended post-operatively [25]. Conversely, other authors found that plates are better implants for proximal femoral fractures than flexible nails [15,16,17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations